EFL INSTRUCTORS’ BELIEFS ABOUT THE IMPLEMENTATION OF SMARTBOARD IN LANGUAGE TEACHING PRACTICES - Rinekso, Aji Budi; Lesagia, Okta (LLT Journal: A Journal on Language and Language Teaching, 2020)
Recently, the use of ICT in today?s English language teaching is quite massive. However, EFL instructors? beliefs about the use of smart boards in language teaching practices are scarcely explored. This study aimed to investigate EFL instructors? beliefs about the implementation of the smart board as ICT-based learning media. Three EFL instructors across English learning centers were voluntarily involved in this study. Observation and semi-structured interviews were employed as the data collection technique. The data were described and interpreted based on the research questions. The results of this study showed that EFL instructors had positive responses towards the implementation of the smartboard. They stated that the smartboard made the explanation clearer and it was not difficult to be operated. Besides, students enjoyed using the smartboard during the lesson. Finally, the EFL instructors agreed that the smartboard could be implemented in classrooms with high control or supervision by the teachers.DOI: doi.org/10.24071/llt.2020.230111